Pengembangan Pola Rithem Tradisi Minangkabau Dalam Proses Penggarapan Karya Musik Dream High - Afri Dino; Syeilendra Syeilendra (SENDRATASIK UNP, 2021)
The use of traditional arts as a working medium in the creation of a musical work is one of the efforts to introduce traditional arts to "modern" people who already consider traditional arts to be out of date. So that the wealth of traditional arts can be lost in the development of the times. The process of developing Minangkabau rhythmic patterns into a musical work that suits the tastes of the community is very interesting to discuss and study. This motivates the creators to develop Minangkabau traditional music materials that can be swallowed up by the times. The process of developing rhythmic patterns includes the development of several rhythmic patterns owned by traditional Minangkabau arts which are spread in several Minangkabau areas. The type of research is qualitative research with a descriptive content analysis approach. Meanwhile, the process of High Dream's work was carried out with an expanded sound vocabulary approach, using media outside of the musical tradition itself. So that Dream High's composition seems to give birth to a distinctive new color without leaving the essence of the rhythmic patterns of Minangkabau traditional music.